Willingness to Communicate: Tracking Movement through Peer Assessment - Niknejad, Sahar; Nazari, Behzad (Communication & Language at Work, 2015)
The purpose of this study was to examine the effect of peer assessment on willingness to communicate (WTC) among Iranian advanced EFL learners in the context of classroom. In order to serve the main purpose of the study, two groups of advanced learners participated in this study. Primarily, a pre-test was administered to both groups, then the participants of experimental group received a treatment of 10 sessions. In these sessions the participants assessed their peers according to the peer assessment form. On the other hand, the participants of control group did not receive any treatment. The quasi-experimental, pre-test, and post-test were applied to these two groups. The obtained data was analyzed with two sample independent t-test statistical methods. The results revealed a meaningful significant difference among Iranian advanced EFL learners' willingness to communicate of the participants who assessed their peer's performances, so peer assessment significantly affected their achievement in oral communication. Teachers deal with learners that are willing to communicate orally in their foreign language, while some learners do not use their foreign language, even with high linguistic competence. Peer assessment can be a good form of assessment to enhance willingness to communicate among EFL learners.